Efektifitas Reaksi Transesterifikasi Minyak Kelapa dan Sereh untuk Pembuatan Perisa Alami dengan Biokatalisator Lipase serta Penggunaan Ultrasonik - Moentamaria, Dwina; Amalia, Nabila Rizki; Rosita Dwi Chrisnandari; Irfin, Zakijah; Wulan, Dyah Ratna (Universitas Andalas, 2024)
In general, flavor are synthesis through enzymatic hydrolysis and esterification reactions (up to 20 hours) using commercial ingredients based on free fatty acids and alcohol. Efficient endeavors utilizing enzymatic transesterification to expedite reactions are necessary to acquire flavored products. Substrates may originate from commercial or natural sources abundant in fatty acids and alcohol. Commercial fatty acids and alcohol (geraniol) are readily available in pure forms. Alternatively, fatty acids can be sourced from coconut oil, while geraniol can be derived from lemongrass oil, which is more cost-effective compared to commercial ingredients. Ultrasonics have emerged as a means to expedite enzymatic. The objective of this study is to investigate the impact of ultrasonic power and transesterification reaction time between coconut oil and geraniol on geraniol conversion. Utilizing lipase (415.99 U/g), coconut oil was subjected to transesterification with commercially obtained pure geraniol in a 1:3 weight ratio, conducted in an ultrasonic tank filled with water. Reaction durations spanned 30, 60, 90, 120, and 150 minutes, with ultrasonic powers set at 50, 70, and 90 watts. The study findings elucidated that the highest geraniol conversion rate of 50.59% was achieved with 70 watts of ultrasonic power over a 90-minute period. These optimal conditions were subsequently applied to transesterify coconut oil with geraniol from lemongrass oil, yielding a conversion rate of 90.29%. This finding demonsttrate the posibility of employing coconut oil and lemongrass oil in a one-stage transesterification process to produce natural flavors via enzymatic lipase catalysis expedited by ultrasonic technology, facilitating swift reaction times.